Reducing Inflation : Lessons From Albania's Early Success - McNeilly, C. (IMF Working Papers; Working Paper ;, 1998)
Inflation in Albania fell rapidly once comprehensive stabilization policies and market-oriented reforms were launched, in contrast to other transition economies, where price liberalization was generally followed by persistently high inflation. The early reduction of underlying inflation is confirmed by trimmed mean estimates of core inflation, which use a central portion of the commodity-wise inflation distribution. This also demonstrates the usefulness of estimating core inflation for transition economies. The early success in curbing inflation is attributed to the extremely broad scope of initial price liberalization coupled with key supporting measures. It also gives hope for early recovery from Albania's 1997 economic crisis.